Comparison of accuracy of determining the distance between alveolar crest and CEJ in digital radiography with two image processing software programs. - Mehdizadeh, Mojdeh; Maarefat, Negar; Nazeri, Rahman (Journal of Isfahan Dental School, 2014)
Introduction: Various techniques are used to diagnose periodontal diseases. Radiography is a useful tool in the diagnosis of periodontal disease, determination of the prognosis and treatment. The aim of this study was to compare the accuracy of determining the distance between the alveolar crest and CEJ in digital radiography with Scanora and Dental Eye software programs. Materials and methods: In this in vitro study 63 sites in a dry human mandible underwent digital periapical radiography. The distance from the alveolar crest to the CEJ was calculated using Dental Eye and Scanora software programs and compared with the standard mode (measured on the skull). Statistical analysis was performed with ANOVA and paired t-test using SPSS 20 at α=0.05. Results: There were significant differences in the distances between CEJ and the alveolar crest at the mesial surfaces as measured by the three techniques of standard mode, Dental Eye and Scanora (p value ≤ 0.03); however, there were no significant differences between the results on distal surfaces (p value = 0.248). Conclusions: Under the limitations of the present study, the measurements made to determine the distance from the CEJ to the alveolar crest with Dental Eye and Scanora, relative to each other, and relative to the standard mode, were accurate only on distal surfaces of teeth.